Hybrid modeling — a key enabler towards realizing digital twins in biopharma?. (December 2021) - Sokolov, Michael; von Stosch, Moritz; Narayanan, Harini; Feidl, Fabian; Butté, Alessandro
Abstract : Digital twins (DTs) represent a vividly emerging technology in the manufacturing industry strongly motivated by the goals of industry 4.0. It strives for smart factories with completely interconnected devices and data archives as well as their automated and adaptive operation based on autonomous decisions of smart algorithms. In this article, we want to provide our vision on the broad potential, critical components as well as current technological and organizational challenges of DTs in biopharma. We put a profound focus on the capability of hybrid modeling as a core technology to realize the capabilities of DTs in the biopharma environment, which is governed by considerable levels of heterogeneity, complexity and uncertainty.